2015
DOI: 10.1111/jdv.13177
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines of care for vascular lasers and intense pulse light sources from the European Society for Laser Dermatology

Abstract: Aim Lasers and non-coherent intense pulse light sources (IPLS) are based on the principle of selective photothermolysis and can be used for the treatment of many vascular skin lesions. A variety of lasers has been developed for the treatment of congenital and acquired vascular lesions which incorporate these concepts into their design. Although laser and light sources are very popular due to their non-invasive nature, caution should be considered by practitioners and patients to avoid permanent side-effects. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
1
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 183 publications
0
41
1
7
Order By: Relevance
“…It was shown previously that objective analysis of the efficacy of treatment of CM gives slightly worse results than subjective methods . Thus, the median maximum improvement obtained in our cohort of previously untreated facial CM reached 70.4% has to be considered as one of the best results available in the literature . Most of the studies conducted on the efficacy of laser treatment for CM included patients with different distribution of skin lesions.…”
Section: Discussionmentioning
confidence: 77%
“…It was shown previously that objective analysis of the efficacy of treatment of CM gives slightly worse results than subjective methods . Thus, the median maximum improvement obtained in our cohort of previously untreated facial CM reached 70.4% has to be considered as one of the best results available in the literature . Most of the studies conducted on the efficacy of laser treatment for CM included patients with different distribution of skin lesions.…”
Section: Discussionmentioning
confidence: 77%
“…This means that different treatment parameters are necessary for different individuals. Laser and photon therapy treatments have been seen to make an effect on vascular dermatoses but as yet have not presented satisfactory results, for example, only 10% of PWS could be completely cured during multiple laser treatments [12] and PDL had no effect on nearly 30% of the lesions.…”
Section: Light and Lasers On Vascular Diseasesmentioning
confidence: 95%
“…Biopsy results showed that vessels in the lateral regions were mainly located in the papillary dermis, whereas in the central regions they tend to expand deeper and run through the dermis into the subcutaneous tissue [44] . In general, however, PWS on the face tend to respond better to the treatment than lesions on the rest of the body [45] . As a whole, the treatment of congenital vascular lesions using laser has been proven to be effective when initiated during the first year of life, something that is partially explained by the fact that the infant's skin is thinner and better penetration of the laser beam within the lesion is achieved [37] .…”
Section: Port-wine Stainsmentioning
confidence: 99%